Pacing strategy and athletic performance - Foster, C.; Schrager, M.; Snyder, A. C.; Thompson, N. N. (Sports Medicine, 1994)
The literature on pacing in athletic performances as well as the types of pacing exhibited in several sports (e.g., running, cycling, speed skating) at Olympic Games competitions were reviewed. pacing is complicated by different physiological mechanisms: a.in short events metabolite accumulation is the primary limitation, and b.in longer events it is substrate depletion which is limiting. Pacing is different for two forms of events: In short duration events, those that are primarily anaerobically energized, it is best to go out fast and come home slower. The effect of pacing errors on performance is more drastic in water and heavily resisted events than in air-resisted events where coasting (recovery) can be effected without too great a cost. In middle distance and longer races, that is, those with aerobic dominance, even pacing is preferable. The pace that is held should promote the greatest mechanical/propelling efficiency as well as maintain supportive anaerobic metabolism at the maximum lactate steady state level. In general though, 50 and 100 m swimming events should have the first half much faster than the second. A value of 5 to 10% drop-off is not an unreasonable expectation. For races longer than 200 m, the pacing should be even with pace in the very final stages of the race being maintained by the final utilization of anaerobic energy sources so that muscle pH levels are lowest at the finish.